Alunos com paralisia cerebral na escola : linguagem, comunicação alternativa e processos comunicativos - Correia, Vasti Gonçalves de Paula (2014)
This study aims at analyzing the contributions of Augmentative and Alternative Communication (AAC) to communicative processes of students with speech disorders in the school setting. It highlights the potentiating role of interlocutors in this process. The investigation is grounded on language approach and the notion discussed by Bakhtin and the contributions of Vygotsky on the relationship between development and learning, positing that language acquisition and development take place during learning, during all the life. The analyses and reflections employed show a discussion about language that departs from an organic dimension towards a dimension of the individual as human being. From this perspective, other concepts such as language, speech, verbal interaction, dialogism, enunciation, learning and development are questioned and also considered fundamental elements that are present in the communicative relations between individuals with speech disorders and their interlocutors. During the first stage, the study seeks to understand organizational-pedagogical methods of five Municipal Education Secretariats in the Metropolitan Area of Vitoria, ES, Brazil and of the State Education Secretariat regarding identification of students with Cerebral Palsy with speech impairment; technical-pedagogical supervision and special education teacher training. In the second stage, the goal is understand the process of pedagogical practice organization instituted in school settings and investigate communicative processes of/with two students with serious motor and speech impairments in two Elementary Schools located in the municipalities of Serra and Vitoria, ES, Brazil. During this stage, the study opted for collaborative critical action research because it contributes theoretically and methodologically to support individual and collective actions in the investigation settings. The results show that, institutionally, the number and identity of students with cerebral palsy with speech disorders are still unknown in the context where their real needs emerge. Municipal Education Secretariat managers attribute this disinformation to the fact that data are generally obtained only from Educacenso-INEP. Localized identification of students with these disabilities derive from inside strategies adopted. One of them is pedagogical assistance to schools. As far as teaching, learning and assessment are concerned, the study verifies that they are permeated by mistaken notions about individuals with cerebral palsy, which is mainly supported by the low expectation from and little effort towards education of these individuals. It is also observed that the use of AAC resources potentiates communicative processes of the students investigated and, pushed by language, they are allowed to express themselves, give opinions and make decisions, which will grant them autonomy and fluency. Mediation by interlocutors as well as the dialogic dynamics they adopt with students constitute important elements in the communication and interaction processes. Waiting for the other, support and encouragement to rephrase what one means, modification and alteration in the dialogic game are examples of this mediation. Concerning actions to reorganize pedagogical practice, the study records more interaction and collaboration between main teacher, Special Education teacher and student-teacher to plan classes and contents after the laptop computer to each student was introduced; the use of communication flashcards by both students and their interlocutors as innovation in school settings; performance of activities by students, with gradual autonomy after TA/AAC resources were made available (folder with theme contents, magnetic pictures, metallic board, pointer, inclined plane, laptop); proposal of intentional literacy action by reorganizing spacetime in school everyday life. The study concludes that theoretical and practical discussions of questions related to language, cognitive processes and use of TA/AAC resources boost changes in school professionals’ concepts. From a reductionist perspective towards communication and verbal intervention, these professionals still "impose" limits to education of students with disabilities